SOCIO CULTURAL PARADIGM OF BRAND TRUST RELATIONSHIP TO PURCHASE INTENTION NU GREEN TEA IN THE VILLAGE OF MENGANTI, GRESIK - Tri Tjahjo Poernomo (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
Abstract This research article aims to identify the positivity of the brand trust relationship (viability dimension & intentionality dimension) to purchase intention. The research sampling consisted of 60 participants who consumed green tea drinks in the village of Menganti, through a judgement sample approach (Cooper & Emory, 2013). There is a positive relationship between brand trust and purchase intention green tea drink of the product, in line with research support that has been carried out by (Fang, Chiu & Wang, 2011). Revealed that there is a positive relationship between brand trust and repurchase intention. H1 & H2 observations can be accepted in the factuality as empiric.